AN ANALYSIS OF STUDENTS GRAMMATICAL ERROR IN WRITING RECOUNT TEXT BY THE EIGHTH GRADE STUDENTS OF SMP N 1 KEMUSU 2023/2024 - Fakihatun, Siska; Handayani, Sri (ENGLISH RESEARCH JOURNAL, 2024)
This study aims to analyze the types of grammatical error of writing recount text. Writing is considered as the most complicated skill to be mastered required not only great vocabularies but also grammar. As Harmer (2004:31) cited in (Wati & Nursyaebah, 2017) states that, when writing, learners often have more time to think than they do in spoken activities. Therefore, they can stimulate their brain, even consult dictionaries, grammar books or other reference material to help them. The researcher used descriptive research. The researcher used written test for students to make a recount text in collecting the data. Test was used to collected the data. The method of this study was descriptive research which was conducted from September until October in 2023/2024 academic year. This subject of the research was students of 8th grade b with 27 students. Miles and Huberman theory was used to analyze the data consisted of data collection, data reduction, data display, and data verification. The result of this research shows that there are two types of errors occurred in this research. The most error is addition (103 or 64%), the second place goes to omission (57 or 36%). In this research can be concluded that addition error type is mostly found in the students‘ writing text. The researcher hope this study can reference students to improve their writing by focusing their errors. This study also provide an overview for teacher to determine the appropriate method in learning. Key words : Error analysis, Grammatical, Writing, Recount text